An English Promotional Video to Show the Well-Rounded Students of Pelangi Kristus Children Seminary - Muh Saifulloh (Kata Kita: Journal of Language, Literature, and Teaching, 2018)
Pelangi Kristuschildren seminaryis a Christian school which runs its educational levels from kindergarten to high school whose curricula and teaching principles are based on biblical perspectives. The competitors of this school are also Christian schools that exist a few meters away, in the same area. Its main problem is the ineffective video that this institution utilizes as a promotional means. To alleviate its promotional video problem, creating one- and two-minute videos which emphasize on independent learners and social excellence are the best solution since this school never makes any short videos that can rebrand its old images. As a result, this company will have such a fresh positive image.